RISK FACTORS LEADING TO DEVELOPMENTAL COMPLICATIONS AFTER OPEN REDUCTION IN DEVELOPMENTAL DYSPLASIA OF HIP - Razaq, Muhammad Naeem ur; Younas, Muhammad; Awan, Abdus Saboor; Waqas, Muhammad; Alam, Muhammad Imran; Khan, Inam ullah (Journal of Ayub Medical College Abbottabad, 2016)
Background: The developmental dysplasia of the hip (DDH) is regarded as one of the commonest congenital deformities. Its incidence has been estimated to be one in 60 live births according to some estimates. Different forms of treatment modalities have been suggested and their success depends on the age of the patient. The study was done with the objectives to observe the post-operative complications of open reduction in patients with DDH and to determine the possible risk factors associated with these complications. Methods: A total of 60 patients were enrolled with DDH in this descriptive cross-sectional study from August 2013 to November 2015. After obtaining an informed consent, the patients underwent open reduction and in some cases, subsequent osteotomy. The patients were followed-up at three months intervals for at least 9 months to look for development of complications, if any. Results: The mean age of the patients was 31.32±2.52 months. Majority 45 (75%) of the study population was female. The most common complication observed was osteonecrosis (5 patients; 8.33%) followed by residual dysplasia and re-dislocation in 3 (5%) patients each. Infection was identified as a complication in 2 (3.33%) patients. When stratified with complications of open reduction, female sex and bilateral hip involvement were found to have a significant association with the development of complications. Conclusion: Female sex and bilateral hip involvement confer a greater risk of developing a complication following open reduction for DDH.